2021
DOI: 10.1007/s10567-021-00349-1
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Parent Training Interventions for Disruptive Behavior Disorders in Treating Untargeted Comorbid Internalizing Symptoms in Children and Adolescents: A Systematic Review

Abstract: Disruptive behavior disorders (DBDs) are among the primary reasons for child and youth referrals to mental health services and are linked to poor adult outcomes including antisocial behavior disorder. Research indicates a high incidence of internalizing problems in those with DBDs and those who have DBDs with cooccurring internalizing problems may have more severe later outcomes. Interventions targeted at internalizing symptoms have been found to also reduce comorbid externalizing problems. The impact of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…This is exempli ed by the contrasting results obtained from our narrative review of individual tests of pre-to post-treatment changes in internalising symptoms across studies versus calculations of pooled treatment effects from meta-analysis. Consistent with previous reviews, ndings from the current narrative review found that only half of included studies favoured BPT over a control or alternative treatment for child internalising symptoms despite small signi cant pooled treatment effects [10]. The contrasting ndings by narrative review allude to the problem that previous clinical trials probably did not possess su cient power to detect small treatment effects.…”
Section: Future Implications For Clinical Trials Evaluating Bptsupporting
confidence: 82%
See 2 more Smart Citations
“…This is exempli ed by the contrasting results obtained from our narrative review of individual tests of pre-to post-treatment changes in internalising symptoms across studies versus calculations of pooled treatment effects from meta-analysis. Consistent with previous reviews, ndings from the current narrative review found that only half of included studies favoured BPT over a control or alternative treatment for child internalising symptoms despite small signi cant pooled treatment effects [10]. The contrasting ndings by narrative review allude to the problem that previous clinical trials probably did not possess su cient power to detect small treatment effects.…”
Section: Future Implications For Clinical Trials Evaluating Bptsupporting
confidence: 82%
“…Comorbid internalising problems are particularly common among externalising children, a icting approximately 20-35% of children in the community and up to 75% of children referred to clinical services [9]. However, current clinical guidelines are limited in specifying the optimal treatment approach in BPT for children with internalising symptoms in the context of externalising behaviours [10]. Previous research has attempted to address this by initially evaluating whether BPT may have crossover effects in improving internalising symptoms, but results are inconsistent [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, internalizing behaviors are characterized as behavioral patterns directed inward toward oneself, including anxiety, fear, sadness/depression, social withdrawal, and somatic complaints [ 1 , 2 , 3 ]. Both behavioral problems co-occur at a high rate among children, and this simultaneous occurrence may be more common than either of them occurring on its own [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Recently, co-occurring emotional and behavioral problems have been reported, and this may be further associated with autism spectrum disorder among children [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…BPT teaches parenting strategies to encourage appropriate behavior and reduce undesired behavior in children (van der Oord & Tripp, 2020). Strategies include communicating with children in ways to increase behavioral compliance, and when and how to reward children for desired behavior in order to increase the likelihood of it being repeated (Zarakoviti et al, 2021). To the best of our knowledge, access to BPT in Brazil is currently very limited, with the most commonly available non-pharmacological intervention being psychoanalysis, especially in public health services (Ortega & Müller, 2020).…”
Section: Introductionmentioning
confidence: 99%